Comparative Efficacy and Safety of Finerenone, Eplerenone, and Spironolactone on Cardiorenal Outcomes in Type 2 Diabetes with Chronic Kidney Disease: A Systematic Review and Network Meta-Analysis - Krismeikesari Krismeikesari (Open Access Indonesian Journal of Medical Reviews, 2026)
Mineralocorticoid receptor antagonists (MRAs) are critical for managing chronic kidney disease (CKD) in type 2 diabetes (T2D), yet a "residual risk" of cardiorenal progression persists. The comparative efficacy and safety of the novel non-steroidal MRA, finerenone, versus the traditional steroidal MRAs, spironolactone and eplerenone, have not been established in a comprehensive analysis. We conducted a network meta-analysis (NMA) to create an evidence-based hierarchy for these three agents. We performed a systematic review searching MEDLINE, Embase, and Cochrane CENTRAL through March 2025 for randomized controlled trials (RCTs) in patients with CKD and albuminuria (predominantly T2D) on baseline renin-angiotensin system (RAS) blockade. We compared finerenone, spironolactone, eplerenone, and placebo. The primary efficacy outcome was the percent change in urinary albumin-to-creatinine ratio (UACR). The primary safety outcome was the relative risk (RR) of hyperkalemia (serum potassium ³ 5.5 mmol/L). A Bayesian random-effects NMA was performed. Seven RCTs involving 15,749 patients were included. For UACR reduction, all MRAs were superior to placebo. Spironolactone (Surface Under the Cumulative Ranking [SUCRA]: 91.2%) and finerenone (SUCRA: 88.5%) were the most effective agents and were statistically indistinguishable. Both were significantly more potent than eplerenone (SUCRA: 58.1%). For hyperkalemia risk, spironolactone was definitively the least safe (SUCRA: 9.5%). Finerenone (RR vs. Spironolactone: 0.63; 95% Credible Interval [CrI]: 0.48–0.82) and eplerenone (RR vs. Spironolactone: 0.65; 95% CrI: 0.45–0.94) were significantly safer. The safety profiles of finerenone (SUCRA: 65.4%) and eplerenone (SUCRA: 62.1%) were comparable.In conclusion, finerenone and spironolactone demonstrate equivalent, superior anti-albuminuric efficacy. However, finerenone uniquely dissociates this high potency from the significant risk of hyperkalemia, offering a safety profile comparable to the less-potent eplerenone. Finerenone, therefore, represents an optimized therapeutic choice, balancing maximal renoprotective efficacy with a superior safety profile for patients with T2D and CKD.